A simple approach for predicting the ultimate lateral capacity of a rigid pile in sand. Issue 3 (31st July 2020) - Wang, H.; Lehane, B. M.; Bransby, M. F.; Wang, L. Z.; Hong, Y.
Abstract : Rigid piles are widely used as foundations to resist lateral load. A calculation to confirm that the ultimate lateral geotechnical capacity of such piles is not exceeded is required for ultimate limit-state design. Existing (empirical) approaches employed to predict the lateral capacity of a rigid pile in sand assume the net soil pressure is a function of the vertical effective stress and friction angle. However, difficulties in determining the appropriate friction angle(s) make these approaches less useful for practical purposes. A simple alternative approach correlated with the cone penetration test end resistance ( q c ) is developed in this paper based on ultimate capacities measured in a new series of tests on rigid piles with diameters of 127, 169, 273 and 457 mm and aspect ratios ( L / D ) between 1·6 and 12. These test results are combined with additional tests reported in the literature to establish a simple formulation for the ultimate net pressure adjacent to a pile in sand. Explicit design equations are also presented for soil profiles with a constant q c value and where q c increases linearly with depth. The proposed equations are seen to provide good estimates of capacities for rigid piles with a wide range of diameters.